Pengaruh Penggunaan Media Video Pembelajaran Interaktif terhadap Hasil Belajar Fisika Siswa SMAN 1 Musi Rawas - Ahmad Fahrudin (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2021)
This research aims to find out the influence of the use of interactive learning video media on the learning outcomes of SMAN1 Musi Rawas Physics. This research uses the Quasi-Experimental Design method with nonequivalent control group design research design. The population of this study was the entire class X SMAN 1 Musi Rawas, with a sample of class XIC as the experimental class and XIA as the control class. Sampling techniques are done randomly. Data collection techniques using tests. Data analysis techniques with t-test. The results showed that, the results of the post-test study physics experimental class the average value was obtained 80.14, the control class was 70.86 and the tcount value was 4.915 > ttable. This means that there is a significant difference between the results of post-test experimental classes that use interactive learning video media and control classes.